UI/UX Design of a Web-Based Student Organizations System Using the Design Thinking Method Approach - Nugroho, Adlan; Purwanto, Joko; Muin, Muhammad Abdul Muin; Mahardika, Fajar (Universitas Dinamika, 2025)
A web-based Student Organization System (Student organizations) is a platform used to manage activities and information about student organizations in higher education institutions. However, in many cases, many existing systems lack an intuitive user interface (UI) and adequate user experience (UX), which causes difficulties in usage and a lack of user engagement. Therefore, this research aims to design a web-based Student organizations system using the Design Thinking method consists of five main stages: Empathize, Define, Ideate, Prototype, and Test. In this study, the first stage was conducted through interviews and surveys with users to understand their problems and needs. The next stage involved defining the identified issues, followed by brainstorming and generating design ideas that fit the requirements. The developed interface prototype was then tested through user testing to evaluate user experience and system functionality. The results of this study were a user interface design that is simpler, easier to navigate, and meets the specific needs of users. Testing of the prototype showed significant improvements in terms of ease of use and user satisfaction. Thus, the Design Thinking approach has proven to be effective in designing a web-based Student organization’s UI/UX system that better aligns with user expectations. The hypothesis test accepted the application with a user reception rate of 86%. Thus, the system falls into the